School facility age and classroom technology: The influence of stakeholder participation in the technology planning process. - Gibson, Huston J. (My University, 2011)
This study begins by examining the relationship between public K-12 school facility age and student access to modern classroom technological resources, driven by questioning “newer equals better” assumptions. The method of analysis employed is multivariate cross-sectional regression. The unit of analysis is the individual school, by school type (elementary, middle, high). Academic school year 2004/05 data are used. The study geography is the Orlando, Florida area (Orange and Seminole Counties). The findings indicate that classroom technology measures, while positively associated with newer school facilities, have no statistically significant relationship with school facility age. Instead, however, having more participants involved in the school technology planning process is found to be the most statistically significant variable included in the model, in relation to greater measures of technology in the school classroom. These findings are intended relevant for educational facility discourse on school facility age and classroom technology.
Keywords: Public school facilities; School facility age; Classroom technology; School technology planning